2021
DOI: 10.3389/fped.2021.702778
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Secondary Hyperparathyroidism and Body Composition in Pediatric Patients With Moderate and Advanced Chronic Kidney Disease

Abstract: Objective: This single center cross-sectional study aims to investigate the association between secondary hyperparathyroidism and body composition in pediatric patients with moderate (stage 3) and advanced (stage 4–5) chronic kidney disease (CKD).Methods: 61 patients (median age: 13.4 years) were included. Body composition indices, including lean tissue index (LTI) and fat tissue index (FTI), were measured using multi-frequency bio-impedance spectroscopy. Muscle wasting was defined as LTI adjusted to height-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The relationship between vitamin D and PTH levels in obesity is complex. Some studies found that the PTH levels are positively associated with the BMI z-score [ 27 , 28 ]. A study conducted in adolescent girls with obesity showed that the ratio of PTH to vitamin D was negatively associated with measures of glucose homeostasis and positively associated with inflammatory markers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between vitamin D and PTH levels in obesity is complex. Some studies found that the PTH levels are positively associated with the BMI z-score [ 27 , 28 ]. A study conducted in adolescent girls with obesity showed that the ratio of PTH to vitamin D was negatively associated with measures of glucose homeostasis and positively associated with inflammatory markers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a U-curve correlation was observed between BMI z-score and pulse wave velocity in a single center study, no association was observed between malnutrition status and carotid intima media thickness in another study on chronic dialysis children [ 28 , 31 ]. Furthermore, limited adult and pediatric studies suggest that overweight patients with moderate CKD may present secondary hyperparathyroidism earlier in the course of the disease, indicating a link between obesity and mineral bone disorders [ 32 , 33 , 34 ]. In the pediatric population, this condition may be more frequent in kidney transplant recipients, where obesity prevalence is higher, as observed in a recent study [ 35 ].…”
Section: Malnutrition Patterns and Outcomes In Children With Ckdmentioning
confidence: 99%
“…Data regarding the prevalence of fat mass loss in CKD pediatric patients are limited. Bioimpedance spectroscopy (BIS)-based body composition assessment revealed that low lean tissue index was observed in 22.6% of patients with moderate CKD and in 36.7% of patients with advanced CKD, while fat tissue index was observed in only 10% of patients with advanced CKD in a cross-sectional study on 61 patients [ 33 ]. Iyengar et al found body fat using Dual-energy X-ray absorptiometry (DXA) and bioimpedance analysis (BIA) was reduced in 18% and 12% of children with CKD 2-5D, respectively [ 73 ].…”
Section: Undernutrition/pew and Muscle Wasting In Children With Ckdmentioning
confidence: 99%